Entrepreneurial Intentions and Entrepreneurial Motivation of South African Rural University Students - Malebana, Mmakgabo Justice (Journal of Economics and Behavioral Studies, 2014)
Entrepreneurial motivation is vital in translating entrepreneurial intention into action. This paper investigates whether entrepreneurial role models, social valuation of entrepreneurship, perceived knowledge of entrepreneurial support and barriers to starting a business, entrepreneurial intention and its determinants are related to entrepreneurial motivation. The study integrates the theory of planned behaviour with environmental factors to determine the factors influencing entrepreneurial motivation among final year rural university students in the Limpopo province, South Africa. The study was carried out by means of a survey and included 329 final year students who were registered for various commerce degrees. A structured questionnaire was used to collect the data. Data were analysed by means of descriptive statistics, Pearson correlation and hierarchical multiple regression analysis. The findings indicate that entrepreneurial motivation has a significant correlation with entrepreneurial intention and its three determinants, social valuation of entrepreneurship, having entrepreneurial role models, knowledge of entrepreneurial support and perceived barriers to starting a business. The respondents were motivated by both intrinsic and extrinsic rewards and the need for independence. The results revealed that entrepreneurial intention, the attitude towards becoming an entrepreneur, subjective norms, social valuation of entrepreneurship, knowledge of entrepreneurial role models and entrepreneurial support have a significant influence on entrepreneurial motivation. This study is the first in South Africa to use theory of planned behaviour to investigate the factors that influence entrepreneurial motivation. The study contributes to the body of knowledge by shedding light into the impact of the social environment on entrepreneurial motivation in South Africa.